PITULIKUR VILLAGE: THE SOCIAL STRUCTURE OF THE COMMUNITY OF ANCIENT BALI IN THE TRADITIONAL VILLAGE OF DUDA, SELAT SUB-DISTRICT, KARANGASEM DISTRICT - Ni Made Widiastuti; I Gusti Ngurah Sudiana; I Nyoman Subagia (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
Pitulikur Village is an ancient community social structure thought to have existed since the mid-17th century. The implementation of aci by Pitulikur Village experienced disharmony and was not satisfactory to the community of Desa Adat Duda. The method of writing is a qualitative description with primary and secondary data sources. The theories used are Structuration Theory and Functional Structural Theory. Factors causing disharmony are internal and external factors that disrupt the balance of energy in sekala and niskala. The role of Pitulikur Village based on Awig-Awig Desa Adat Duda is to organize Aci Usaba Emping, Usaba Kapat, Usaba Bangket, Aci Mendak at Ulun Siwi Temple, Metabuhin, and Aci Usaba Dalem. Pitulikur Village functions according to the concept of Catur Lawa and Prasadam Bangun Urip; namely, Pasek functions as a mass mobilizer in prasadam getting puspusan / feet. Kebayan functions to organize, manage resources. In prasadam get polo/brain. Penyarikan functions as secretary, in prasadam gets ikuh/tail. Members/Jro Desa get prasadam in addition to feet, brain, and tail. This research found that the existence of Pitulikur Village strengthens the organization of aci in Desa Adat Duda, because it gets the legality of authority both in sekala and niskala through the existence of sacred buildings of Pasek, Kebayan, and Penyarikan in the main mandala of Pura Puseh and Pura Desa (Bale Agung). The organization of aci can be harmonious with the functioning of agil.